Time and quality of 3D rendering process using programming code optimisation techniques. (26th September 2008) - Choros, Kazimierz; Kaczynski, Krzysztof
Rendering is a process of generating photorealistic images on the basis of geometrical models. If such a process is performed so fast that the changing images form a dynamic, continuous movie, we call it a real-time rendering. The paper presents the results of exhaustive testing of computing time and subjective estimation of quality of 3D photorealistic rendering. The tests have shown that the effectiveness of these methods depends on the number of 3D model triangles, the object scale, and the number of moving light sources. The computing time can be significantly reduced if we apply some programming code optimisation techniques.